Carcinoma prostate with intradural metastasis: A case report and review of the literature on a rare entity with dismal prognosis - Sahoo, Bijayalaxmi; Panda, Niharika; Kumar Barik, Sandip; Patra, Abinash Chandra (Indian Journal of Case Reports, 2020)
Prostate carcinoma is the second most common cancer in men. While bone metastasis is more common in carcinoma prostate, dural metastasis is an uncommon diagnosis. Nowadays, men with castration-resistant prostate cancer (CRPC) have shown increase survival with the introduction of better chemotherapy regimens. Here, we present the case of a heavily pre-treated CRPC patient of age 69-year-old who developed metastasis to dura mater. The patient presented with complaints of increased urinary frequency and urgency with bilateral inguinal lymphadenopathy. The ultrasonography-guided biopsy showed acinar adenocarcinoma of the prostate with a Gleason score of 4 + 4 = 8 and TNM staging of T1N3M1b. He was treated initially with hormonal therapy. Subsequently, he developed castration resistance and was advised docetaxel-based chemotherapy. However, on follow-up, the patient developed dural metastasis. Metastases to dura mater should be considered as a differential diagnosis in advanced CRPC with neurological symptoms.